Taxes and Charges in Road Freight Transport – a Comparative Study of the Level of Taxes and Charges in the Slovak Republic and the Selected EU Countries - Vladimír Konečný; Štefánia Semanová; Jozef Gnap; Ondrej Stopka (Naše More (Dubrovnik), 2018)
The paper deals with the issue of taxes and charges in road freight transport in the Slovak Republic and the selected European countries. The aim is to compare and evaluate the position of the Slovak carriers towards foreign ones when doing business in the common European market. The selected kinds of taxes and charges (or costs items) relate to different production factors of road transport undertakings (vehicles, drivers, road infrastructure). Also, the legislation on taxes and charges differs among individual countries and differences can be observed in the principles of taxation. The objective is to make a comprehensive objectified comparison when taking into account several selected taxes, charges and costs in road transport.